Clinal variation in developmental time and viability, and the response to thermal treatments in two species of Drosophila - Folguera, G. (2008)
The present study first addressed the question of whether developmental time (DT) and viability (VT) vary clinally along latitudinal and altitudinal gradients in Drosophila buzzatii, an autochthonous specialist and the generalist invasive Drosophila melanogaster. Coincident and positive altitudinal clines across species and, direct and inverse latitudinal clines were observed for DT in D. melanogaster and D. buzzatii, respectively. Opposing latitudinal and altitudinal clines were detected for VT only in D. melanogaster. The patterns observed along altitudinal gradients prompted us to investigate whether flies living at lowland and highland environments may respond differentially to thermal treatments consisting of regimes of constant and alternating temperatures. Flies reared at higher mean temperature developed faster than at lower mean temperature in both species. By contrast, the response in VT differed greatly between species. Highland D. melanogaster were more viable than lowland regardless the treatment, whereas, in D. buzzatii, highland flies were more viable than lowland in alternating thermal regimes and the reverse was true in treatments of constant temperature. The results obtained suggest that thermal amplitude may be an important factor that should be considered in investigations of thermal adaptation. © 2008 The Linnean Society of London.